Selective deletion of SHIP-1 in hematopoietic cells in mice leads to severe lung inflammation involving ILC2 cells - Xujun Ye (Nature Portfolio, 2021)
Abstract Src homology 2 domain–containing inositol 5-phosphatase 1 (SHIP-1) regulates the intracellular levels of phosphotidylinositol-3, 4, 5-trisphosphate, a phosphoinositide 3–kinase (PI3K) product. Emerging evidence suggests that the PI3K pathway is involved in allergic inflammation in the lung. Germline or induced whole-body deletion of SHIP-1 in mice led to spontaneous type 2-dominated pulmonary inflammation, demonstrating that SHIP-1 is essential for lung homeostasis. However, the mechanisms by which SHIP-1 regulates lung inflammation and the responsible cell types are still unclear. Deletion of SHIP-1 selectively in B cells, T cells, dendritic cells (DC) or macrophages did not lead to spontaneous allergic inflammation in mice, suggesting that innate immune cells, particularly group 2 innate lymphoid cells (ILC2 cells) may play an important role in this process. We tested this idea using mice with deletion of SHIP-1 in the hematopoietic cell lineage and examined the changes in ILC2 cells. Conditional deletion of SHIP-1 in hematopoietic cells in Tek-Cre/SHIP-1 mice resulted in spontaneous pulmonary inflammation with features of type 2 immune responses and airway remodeling like those seen in mice with global deletion of SHIP-1. Furthermore, when compared to wild-type control mice, Tek-Cre/SHIP-1 mice displayed a significant increase in the number of IL-5/IL-13 producing ILC2 cells in the lung at baseline and after stimulation by allergen Papain. These findings provide some hints that PI3K signaling may play a role in ILC2 cell development at baseline and in response to allergen stimulation. SHIP-1 is required for maintaining lung homeostasis potentially by restraining ILC2 cells and type 2 inflammation.